2020
DOI: 10.3389/fcomp.2020.601271
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Skeleton Avatar Technique for Assessment of Mobility and Balance Among Older Adults

Abstract: Background: Mobility and balance is essential for older adults' well-being and independence and the ability to maintain physically active. Early identification of functional impairment may enable early risk-of-fall assessments and preventive measures. There is a need to find new solutions to assess functional ability in easy, efficient, and accurate ways, which can be clinically used frequently and repetitively. Therefore, we need to understand how functional tests and expert assessments (EAs) correlate with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 38 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…A large dataset will open up the possibility of testing additional classifiers and retesting the classifiers that are already tested and mentioned in this paper. Commonly used deep ML methods on skeletal data such as Convolutional Neural Network (CNN) [ 44 ] and Recurrent Neural Network (RNN) [ 45 ] will also be attempted in order to verify their usability with the proposed and additional set of skeletal parameters for skill assessment. Skeletal features that were not considered in this paper will also be tested for usability in these classifiers.…”
Section: Discussion and Future Directionmentioning
confidence: 99%
“…A large dataset will open up the possibility of testing additional classifiers and retesting the classifiers that are already tested and mentioned in this paper. Commonly used deep ML methods on skeletal data such as Convolutional Neural Network (CNN) [ 44 ] and Recurrent Neural Network (RNN) [ 45 ] will also be attempted in order to verify their usability with the proposed and additional set of skeletal parameters for skill assessment. Skeletal features that were not considered in this paper will also be tested for usability in these classifiers.…”
Section: Discussion and Future Directionmentioning
confidence: 99%
“…In this study, we have used assessment and measurement results collected from our previous studies 1,6 as shown on Figure 1. It includes: three supervised FTs (TUG, 30sCST, and 4SBT) performed in a controlled environment, EA of the sit-to-stand movement performed on video recordings by an experienced physiotherapist using the Instrument for movement analysis of person transfer and mobility (IRAF) in daily living, 8 daily life PA collected by an ActivPAL device within 7 days, and completed SA questionnaire about daily life PA.…”
Section: Methodsmentioning
confidence: 99%
“…In order to compare the 2D SAT with the 3D SAT approaches, we applied the same number of experiments (8 settings: indirect/direct features, cut/uncut sequences, normalized/not normalized features) with the same deep-learning models: convolutional neural network (CNN) and recurrent neural network (RNN) as in our previous studies, 1,6 and shown on Figure 2.
Figure 2.Machine learning experiments overview.
…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations